Abordagem termodinâmica do transporte iônico e da relaxação estrutural em vidros fosfatos de prata - Bragatto, Caio Barca (2016)
Ionic conductivity in glasses was first discovered and demonstrated by Warburg in 1884, but although it has been studied for over a century, the mechanisms underlying ionic conduction in glasses are not yet entirely clear. Glasses are commonly known to be electrical insulators, but some of them may present high conductivity and be candidates for different applications. The more conductive glasses result from the dissolution of halogenated salts in the glassy matrix, causing its ionic conductivity to increase by several orders of magnitude. Our approach proposes that glass can be compared to a solution in which a dissolved halogenated salt (solute) is weakly dissociated in the glassy matrix (solvent). This approach, called the weak electrolyte model, was initially proposed in the 70s to explain the almost exponential increase in the ionic conductivity of glasses in response to increasing concentrations of network modifiers (alkaline oxides). Our work proposes to expand this approach, correlating the increase in ionic conductivity with the increase in the thermodynamic activity of AgI. In addition, experiments were carried out at different temperatures in various glass compositions to confirm this correlation, using electromotive force (EMF) measurements to determine the thermodynamic activity and electrochemical impedance spectroscopy (EIS) measurements to determine the ionic conductivity of these glasses. Ionic transport was also used to examine the structural relaxation of AgPO3 glass. The glass was heated to another fictive temperature in the glass transition range and its ionic conductivity measured in situ by EIS. The kinetic parameters of the structural relaxation process, i.e., structural relaxation time ( ) and stretching parameter (β), were determined as a function of time by fitting the experimental data to KWW equations.